Электрические и фотоэлектрические свойства гетероструктур NiO/p-CdTe и NiO/n-CdTe - Пархоменко, Г.П.; Марьянчук, П.Д. (Технология и конструирование в электронной аппаратуре, 2016)
Изготовлены гетероструктуры NiO/n-CdTe и NiO/p-CdTe методом реактивного магнетронного напыления тонких пленок оксида никеля на подложки из кристаллов CdTe p- и n-типа проводимости, исследованы их темновая и световая вольт-амперные характеристики. Установлено, что основными механизмами токопереноса при прямом смещении является генерационно-рекомбинационный и туннелирование, при обратных смещениях — туннелирование. Методом реактивного магнетронного напилення тонких плівок NiO на підкладки з кристалів CdTe p- та n-типу провідності виготовлено гетероструктури NiO/n-CdTe та NiO/p-CdTe. Досліджено їх темнову і світлову вольт-амперні характеристики. Встановлено, що основними механізмами струмопереносу при прямому зміщенні є генераційно-рекомбінаційний і тунелювання, при зворотньому — тунелювання. In this study, we investigate the electrical and photoelectric properties of heterostructures formed by the reactive magnetron sputtering of thin film NiO onto p-CdTe and n-CdTe substrates. The current-voltage characteristics of the heterojunctions were measured at room temperature. The dominating current transport mechanisms through the NiO/n-CdTe and NiO/p-CdTe heterojunctions at the forward biases are generation-recombination and tunnel, at the reverse biases is tunnel current transport mechanisms. The heterojunctions under investigation generate open-circuit voltage Uoc = 0.26 V and short-circuit current Isc = 58.7 μA/cm² under illumination 80 mW/cm⁻². The research results can be used for better understanding of the processes occurring in heterojunctions NiO/ n-CdTe and NiO/p-CdTe, to further improve their properties and parameters.